Budaya Literasi Sebagai Upaya Pembentukan Pendidikan Karakter - Frysca Amanda Putri; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
Literacy plays an important role in shaping student character, with a literacy culture that includes reading and writing habits. Literacy culture helps shape characters such as honesty, responsibility and independence, which are key values ​​in student development. Familiarization with literacy activities, developing interest in reading, and implementing literacy-based learning are concrete steps in building student character. The research method used is literature review. Research results show that literacy culture can improve reading, writing, arithmetic skills and instill character values.